2006
DOI: 10.4049/jimmunol.177.5.3355
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Hormone Receptor 2-Deficient Mice Have Reduced Intestinal Inflammatory Responses

Abstract: Corticotropin-releasing hormone (CRH) and urocortins (Ucn) bind with various affinities to two G-protein-coupled receptors, CRHR1 and CRHR2, which are expressed in brain and in peripheral tissues, including immune cells. CRHR2-deficient mice display anxiety-like behavior, hypersensitivity to stress, altered feeding behavior and metabolism, and cardiovascular abnormalities. However, the phenotype of these mice in inflammatory responses has not been determined. In the present study we found that compared with wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
85
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 54 publications
10
85
1
2
Order By: Relevance
“…Our previous studies on the role of additional neuropeptides such as substance P, neurotensin, and members of the corticotropinreleasing hormone (CRH) family of peptides in intestinal inflammation demonstrated that receptors for these molecules are expressed in intestinal epithelial cells and their expression is increased during the course of inflammation (30)(31)(32)(33)(34). Hence, to examine epithelial cell expression of MCH and its receptors, we used a laser capture microdissection (LCM) approach to isolate colonic epithelial cells from cryopreserved surgical specimens obtained from patients with IBD and controls (35).…”
Section: Mch Functional Receptors Are Expressed In Colonocytesmentioning
confidence: 99%
“…Our previous studies on the role of additional neuropeptides such as substance P, neurotensin, and members of the corticotropinreleasing hormone (CRH) family of peptides in intestinal inflammation demonstrated that receptors for these molecules are expressed in intestinal epithelial cells and their expression is increased during the course of inflammation (30)(31)(32)(33)(34). Hence, to examine epithelial cell expression of MCH and its receptors, we used a laser capture microdissection (LCM) approach to isolate colonic epithelial cells from cryopreserved surgical specimens obtained from patients with IBD and controls (35).…”
Section: Mch Functional Receptors Are Expressed In Colonocytesmentioning
confidence: 99%
“…26,27 Central release of CRF and urocortins mediates autonomic, hormonal, and behavioural responses to stress and at the gastrointestinal tract, stimulates the enteric nervous system to modulate gastrointestinal motility and secretion. [28][29][30] In addition, immune cells, regional sensory and sympathetic nerves, enterochromaffin cells, and enteric cells release CRF and urocortins within the gastrointestinal tract 28 to modulate mucosal function and gastrointestinal motility. 29 Different type of stress, acute or chronic, physical or psycho-logical, have been shown to influence properties of the intestinal barrier function, including ion and water secretion, intestinal permeability, mucus secretion, and also intestinal flora in both human and animal models.…”
Section: Stress-induced Intestinal Barrier Dysfunction: Role Of Cortimentioning
confidence: 99%
“…19 Moreover, enterotoxin-induced ileitis was reduced in CRF 2 receptor-deficient mice or the CRF 2 receptor specific antagonist astressin 2-B -treated mice along with decreased mRNA expression levels of keratinocyte chemokine and monocyte chemoattractant protein 1. 15 Additionally, CRF 2 receptor activation by Ucn2 treatment was able to stimulate the expression of IL-8 and monocyte chemoattractant protein 1 in human colonic epithelial HT-29 cells expressing CRF 2 receptor. 15 In line with this, RNA interference of CRF 2 receptor but not CRF 1 receptor dramatically reduced the extent of ulceration during colitis.…”
mentioning
confidence: 99%
“…15 Additionally, CRF 2 receptor activation by Ucn2 treatment was able to stimulate the expression of IL-8 and monocyte chemoattractant protein 1 in human colonic epithelial HT-29 cells expressing CRF 2 receptor. 15 In line with this, RNA interference of CRF 2 receptor but not CRF 1 receptor dramatically reduced the extent of ulceration during colitis. 20 It is noteworthy that the expression of the CRF family and its receptor was altered in the inflammatory tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation